Compressive strength values dispersion of side-mixed and ready-mixed concretes - ALVES,A. (2017)
Abstract Compressive strength testing method has been widely used as indirect way for evaluate the concrete quality, due to it simplest execution, reliability of the results achieved and low cost of execution. Independently, if the concrete was side or ready-mixed, it is necessary to achieve the compressive strength requirements stated during structure design, essentially because this parameter allows the obtainment of the average strength of the reinforced concrete structure analyzed. Following, as for ready-mixed, as for side-mixed concretes, it is need to ensure the correspondence between the concrete design parameters and the concrete mixed, namely these parameters are summarized in terms of the compressive strength and homogeneity in the different phases of the construction. This way, the present work aims to do the analysis of the dispersions of the compressive strength of concretes mixtures (corresponding to compressive strength classes of 20, 25, 30, 35 and 40 MPa), and identify some influence factors, in this case, the influence of the workers team variation. Two mixtures (35 MPa and 40 MPa) were ready-mixed, while five of the concrete mixtures were side-mixed, by five different worker’s group with same time of experience on concrete’s manufacture. The results demonstrate that the variation of the workers team presents a high influence for the homogeneity of the compressive strength of the concrete.